Dampak Penetapan Izin Praktek Tambang Emas Tumpang Pitu Perspektif Fikih Sosial KH. Sahal Mahfudh - Mun'im, Zainul (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2024)
Abstract: Due to its significant impact on the environment, gold mining is often a particular concern. This paper examines the effect of granting gold mining permits on Mount Tumpak Pitu, Banyuwangi Regency, East Java, from the perspective of social fiqh developed by Sahal Mahfudh. Social fiqh prioritizes benefits framed in maqâshid al-syarî'ah, with indicators of hifz al-dîn (existence of religion), al-nafs (salvation of the soul), al-'aql (health of the mind), al-mâl (safety of property), al-nasl (safety of honor) and al-bî'ah (environmental sustainability). This research used the normative juridical approach and qualitatively analyzed data collected through literature and field studies. The research results show that granting gold mining permits was not accompanied by adequate supervision from the authority. This gives rise to mining practices that are not environmentally friendly and do not fulfill the basic principles of environmental ethics in Sahal Mahfudh’s social fiqh.Abstrak: Penambangan emas seringkali menjadi perhatian khusus mengingat aktvitas tersebut memiliki dampak yang signifikan terhadap lingkungan. Tulisan ini mengkaji dampak pemberian izin penambangan emas di Gunung Tumpak Pitu, Kabupaten Banyuwangi, Jawa Timur; dari perspektif fikih sosial yang dikembangkan oleh KH Sahal Mahfudh. Fikih sosial mengedepankan kemaslahatan yang dibingkai dalam maqâshid al-syarî'ah, dengan indikator hifz al-dîn (eksistensi agama), al-nafs (keselamatan jiwa), al-‘aql (kesehatan akal), al-mâl (keselamatan harta), al-nasl (keselataman kehormatan) dan al-bî’ah (kelestarian lingkungan). Dengan pendekatan juridis normatif terhadap data-data yang dikumpulkan baik melalui studi kepustakaan maupun lapangan dan dianalisis secara kualitatif, hasil penelitian menunjukkan bahwa pemberian izin penambangan emas yang diberikan tidak diiringi dengan pengawasan yang memadai. Hal tersebut menimbulkan praktek pertambangan yang tidak ramah lingkungan dan tidak memenuhi prinsip dasar etika lingkungan dalam fikih sosial KH. Sahal Mahfudh.